Keratoacanthoma centrifugum marginatum: report of a rare variant of keratoacanthoma - Tiecher, Gabrieli Budke; Bezerra, João Victor; Filitto, Beatriz Freitas; de Abreu, Marilda Aparecida Milanez Morgado; Miot, Hélio Amante [UNESP]; Espósito, Ana Claudia Cavalcante [UNESP] (GN1 Sistemas e Publicacoes, 2023)
We report a case of a 72-year-old man who underwent surgical excision of a keratoacanthoma centrifugum marginatum (KCM) located on the left forearm. It is an uncommon variant of keratoacanthoma, which can assume large dimensions (up to 20 cm) and does not tend to spontaneous regression. The lesion is usually single, with raised borders, and has progressive centrifugal growth associated with central healing and atrophy. Due to its rarity and lack of pathognomonic histopathological features, KCM can be a diagnostic challenge for dermatologists and pathologists.
Queratoacantoma centrífugo marginado: relato de uma variante rara de queratoacantoma
Keywords: Keratoacanthoma; Neoplasms; Skin neoplasms